QUANTITATIVE STRATEGIC PLANNING MATRIX PADA PENJUALAN KOPI BUBUK SUKASARI COFFEE DI BENGKULU - Selvia, Selvia; Via, Sel; Yumiati, Yossie; Yulihartika, Rika Dwi (University of Prof. Dr. Hazairin, SH, 2024)
In the Kepahiang Regency area in Kabawetan District, there is a coffee business called Sukasari Coffee which makes processed robusta coffee into ground coffee. Increasingly tight competition with similar businesses makes it difficult for Sukasari Coffee to enter the market. So a strategy is needed to increase sales of Sukasari Coffee ground coffee in Kabawetan District. This research was conducted to (1) find out the strengths, weaknesses, opportunities and threats in the SWOT Analysis that influence the increase in Sukasari Coffee Ground Coffee Sales. (2). To find out how to formulate a marketing strategy using the Quantitative Strategic Planning Matrix (QSPM) method to increase Sukasari Coffee Ground Coffee Sales. This research uses a quantitative method using a questionnaire. The research was conducted purposively at Sukasari Coffee which is in Sukasari Village, Kabawetan District. The analysis used includes IFE, EFE, and QSPM. The research results show that the internal factor that is the main strength for ground coffee business actors is the high quality of the ground coffee. The main weakness factor is limited distribution. The external factor that is the biggest opportunity for business actors is market expansion or the development of new markets. Threatening factors are changes in policies and regulations. Sukasari Coffee chose the right strategy to increase sales of ground coffee, offering ground coffee products at varying prices through an e-commerce platform with a strong promotional strategy by utilizing wide access and reach from online sales with a TAS value of 6,127.